Religion and Public Reason: A Comparison of the Positions of John Rawls, Jürgen Habermas and Paul Ricoeur - Junker-Kenny, Maureen (Praktische Theologie im Wissenschaftsdiskurs, 2014)
Biographical note: Maureen Junker-Kenny, Trinity College, Dublin, Ireland.